2018
DOI: 10.2337/dc18-1122
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of the Glucose Response Curve During an Oral Glucose Tolerance Test: Forerunner of Heightened Glycemic Failure Rates and Accelerated Decline in β-Cell Function in TODAY

Abstract: Obese youth without diabetes with monophasic oral glucose tolerance test (OGTT) glucose response curves have lower insulin sensitivity and impaired b-cell function compared with those with biphasic curves. The OGTT glucose response curve has not been studied in youth-onset type 2 diabetes. Here we test the hypothesis that the OGTT glucose response curve at randomization in youth in the TODAY (Treatment Options for Type 2 Diabetes in Adolescents and Youth) study forecasts heightened glycemic failure rates and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 26 publications
6
50
0
Order By: Relevance
“…In studies of nondiabetic individuals, the morphology of the monophasic glucose response curve is the dominant phenotype, up to 57–84% in adults [12, 13, 17, 22, 23] and 35–69% in obese youth at high risk for T2D [6, 7, 9, 10, 24]. Our study showed that about 88.3% of individuals had monophasic response curves and 11.7% had multiphasic response curves.…”
Section: Discussionmentioning
confidence: 58%
“…In studies of nondiabetic individuals, the morphology of the monophasic glucose response curve is the dominant phenotype, up to 57–84% in adults [12, 13, 17, 22, 23] and 35–69% in obese youth at high risk for T2D [6, 7, 9, 10, 24]. Our study showed that about 88.3% of individuals had monophasic response curves and 11.7% had multiphasic response curves.…”
Section: Discussionmentioning
confidence: 58%
“…Following the immediate period around diagnosis, T1D is characterized by progression to complete insulin deficiency beyond the partial remission, or “honeymoon” period 62 . T2D is defined by insulin resistance, with typically elevated C‐peptide and insulin concentrations in the early stages of the disease 63 and gradual decline of beta cell function over time 62,64 . As mentioned above, patients with T2D may need insulin at diagnosis if they present with DKA or very high HbA1c level.…”
Section: Pitfalls Of the Current Classification Of Diabetes In Childrenmentioning
confidence: 99%
“…The present investigation revealed the following findings regarding the shape of OGTT curve in a large Chinese population: 1) multiphasic OGTT response curves were not rare in Chinese people, accounting for more than 10% of the population; 2) monophasic curves were more common in older In studies of nondiabetic individuals, the morphology of the monophasic glucose response curve is the dominant phenotype, up to 57-84% in adults [12,13,17,22,23] and 35-69% in obese youth at high risk for T2D [6,7,9,10,24]. Our study showed that about 88.3% of individuals had monophasic response curves and 11.7% had multiphasic response curves.…”
Section: Discussionmentioning
confidence: 60%